Analyzing urban water metabolism of Adama city using water mass balance method for advancing water sensitive interventions - Tesfay, Abraha; Assefa, Tibebu; Gebremariam, Ephrem (Frontiers in Water, 2024)
Urban water metabolism focuses on measuring water inflows and outflows within a defined urban system. As an emerging concept, it provides valuable understandings into water flow dynamics, supporting evidence-based decision-making. One approach to quantify these flows is the urban water mass balance method, which accounts for both human-induced and natural water resources. By equating these flows, it identifies whether water movement within the system is linear or circular. The primary goal of water mass balance analysis is to assess how closely a city aligns with water-sensitive management approaches. However, urban metabolism studies are rare in developing countries, where cities often lack the experience to estimate water inflows and outflows for informed water-sensitive interventions. This study addresses this gap by analyzing Adama city in Ethiopia using the water mass balance method to measure its water metabolism. The result revealed that the city faces a negative water balance with outflows exceeding inflows by 46.89 million cubic meters annually. The results indicated that Adama’s water flow follows a linear “take-make-use-dispose” model. The imbalance in Adama’s water cycle is driven by urbanization, impervious surfaces, and climate change, which increase runoff and evaporation. The study found that 61.3% of the city’s water comes from a centralized system, with 90% sourced from distant rivers through a telecoupling system. In the city, inadequate water harvesting, high population density and intensive water use are worsening water scarcity. Urban water metabolism indicators reveal significant losses and indicating the need for water conservation efforts. Despite the reliance on centralized systems, the study identifies strong potential for decentralized solutions and alternative water harvesting. To tackle these challenges, the research recommends adopting water-sensitive strategies such as low-impact development, sustainable urban drainage systems, and water-sensitive urban design and planning. These approaches can reduce the negative effects of urbanization, mitigate urban water scarcity risks and improve water management through water sensitive management approach. The study also emphasizes the need for collaborative learning, community involvement, and innovative technologies, supported by legal frameworks to ensure effective water wise interventions. Shifting toward circular water management and decentralized water systems will boost Adama’s resilience and promote sustainable water resource management, making the city more internally self-sufficient.